Irrational Beliefs and Their Relationship with Optimism and Pessimism among Female Students of the Faculties of Arts and Science at Al-Asmariya Islamic University, Zliten: Irrational Beliefs and Their Relationship with Optimism and Pessimism (Journal of Humanitarian and Applied Sciences, 2026)
This study aimed to examine the relationship between irrational beliefs and levels of optimism and pessimism among female students of the Faculties of Arts and Science in Zliten. The researcher adopted a descriptive correlational-comparative approach. The study sample consisted of 129 female students. Irrational beliefs were measured using the Al-Rihani Scale (1985), while optimism and pessimism were assessed using the Abdel-Khalek Scale (1996).      The findings revealed that the prevalence of irrational beliefs was low among students of both faculties, reaching 56% among Faculty of Arts students and 58% among Faculty of Science students. The level of optimism was high, amounting to 75% among Faculty of Arts students and 80% among Faculty of Science students. The results also indicated a statistically significant negative correlation between irrational beliefs and optimism, and a corresponding positive association between irrational beliefs and pessimism. Furthermore, no statistically significant differences were found in irrational beliefs between students of the two faculties attributable to academic specialization. However, significant differences in optimism were observed in favor of Faculty of Science students. In contrast, no statistically significant differences were found in pessimism between students of the Faculties of Arts and Science.
Keywords: Irrational Beliefs; Optimism and Pessimism; Female Students; Faculty of Arts; Faculty of Science; Zliten